El papel de Mxico en la construcción de un nuevo enfoque de la cooperación para el desarrollo: perspectivas para la agenda del G20 sobre desarrollo - Soria Morales, Ernesto (Revista Española de Desarrollo y Cooperación, 2023)
Mexico will chair the Group of Twenty (G20) from November 2011. This provides Mexico with a unique opportunity to consolidate its “bridge” role between two major traditions of international development cooperation —North-South and South-South— and contribute to a broader and strategic agenda that goes beyond “aid effectiveness” towards “development effectiveness”. This change is a necessary response to an international context characterized by structural transformations in global economy and the recognition to the imperative to advance towards more holistic and inclusive approaches on development co-operation to produce greater impact.